Suppressed convective rainfall by agricultural expansion in southeastern Burkina Faso. Issue 7 (19th July 2015) - Mande, Theophile; Ceperley, Natalie C.; Katul, Gabriel G.; Tyler, Scott W.; Yacouba, Hamma; Parlange, Marc B.
Abstract With the "green economy" being promoted as a path to sustainable development and food security within the African continent, the influx of agricultural land is proliferating at a rapid pace often replacing natural savannah forests. Where agriculture is primarily rainfed, the possible adverse impacts of agricultural land influx on rainfall occurrences in water‐limited areas such as West Africa warrant attention. Using field observations complemented by model calculations in southeastern Burkina Faso, the main causes of a 10–30% suppressed daytime rainfall recorded over agricultural fields when referenced to natural savannah forests are examined. Measurements and model runs reveal that the crossing of the mixed layer height and lifting condensation levels, a necessary condition for cloud formation and subsequent rainfall occurrence, was 30% more frequent above the natural savannah forest. This increase in crossing statistics was primarily explained by increases in measured sensible heat flux above the savannah forest rather than differences in lifting condensation heights.